ANALISIS STRUKTUR DIKSI PADA PUISI “PADAMU JUA” KARYA AMIR HAMZAH - Muhamad Mahdar; Yuliana Tika Tri Amalia; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to (1) describe the structure of diction on the poetry "Padamu Jua" by Amir Hamzah using structural analysis method. Poetry "Padamu Jua" is examined through data collection steps; (1) intensive reading of poetry "Padamu Jua", in (2) analyzing the structure of diction and describing it. After going through the process of structural analysis research, it appears that Amir Hamzah's effort to write this poem "Padamu Jua" selects certain words that are closely related to artistic expression of ideas.